Penyelenggaraan Sistem Informasi Manajemen Administrasi Umum dalam Rangka Mendukung Tugas Tentara Nasional Indonesia Angkatan Udara - Triyanto, Triyanto; Marsono, Marsono; Eko, Bambang (Journal of Law & Policy Review, 2025)
The Air Force General Secretariat is part of the staff service element that functions under the Air Force Chief of Staff to manage the general administration system within the Air Force Headquarters. In carrying out its duties, the Air Force General Secretariat is responsible for carrying out general administration at the Air Force Headquarters level. The Air Force General Secretariat has a role in supporting leadership administration by managing correspondence, compiling manuscripts, providing support to working groups, recording minutes, and providing data and information needed for decision making. In carrying out its duties, the Air Force General Secretariat has implemented a general administrative management information system. This research discusses the implementation of a general administration management information system that supports the duties of the Indonesian Air Force, but its implementation is not yet optimal. This research uses a qualitative method with a narrative design. The results of the research show that the Air Force General Secretariat faces several obstacles in implementing the general administration management information system, such as limited capabilities of the personnel manning it, infrastructure facilities and infrastructure and the absence of software, which causes support for the implementation of the duties of the Indonesian National Army Air Force to be less than optimal. Therefore, steps are needed to overcome these obstacles so that the implementation of the general administration management information system can run optimally.